The Potential of Forestry Sector Waste for Biochar Production: Characteristics and Production Challenges - Sumiati Simanullang; Riki Andika; Yunia Frida Adelka; Saviska Luqyana Fadia; Muhammad Rasyidur Ridho (Westscience Press, 2025)
Timber harvesting has long been the primary focus of forest utilization as a major economic resource, yet more efficient strategies are needed to reduce excessive logging by implementing measured harvesting and maximizing the use of all wood components. Branches, logging residues, sawmill by-products, and discarded wooden furniture remain underutilized and are often treated as waste. These materials have high potential to be converted into value-added products such as biochar. Forestry waste is particularly suitable as a feedstock for biochar due to its lignocellulosic richness. Biochar is a carbon-rich material produced through pyrolysis. Biochar derived from forestry waste has significant potential to improve soil structure and water-holding capacity, while also contributing to long-term carbon storage and climate change mitigation. However, challenges remain, including variability in biochar quality, absence of global standards, high production costs, contaminant risks, and limited formal guidelines.